Implementation of Anti-Corruption Education In Learning Citizenship Education for Students in Elementary Schools - Yanti, Nelmida (International Journal of Students Education, 2024)
Education is the beginning of forming someone to be better with education also someone can form themselves away from reprehensible things, such as corruption. Corruption is an act of someone who wrongly abuses trust in a problem or organization to take advantage. Corruption is a criminal act that harms state finances. This study aims to examine, find basic ideas of the theoretical conceptual framework and implementation of anti-corruption education through learning Civic Education in elementary school students. The method used in this study is a research method with a qualitative approach that is descriptive. Data collection techniques are carried out by means of literature studies from various sources such as books, journals and others. The results of this study are Factors that support the development of student character through anti-corruption education are divided into two categories, namely internal and external. The development of syllabus, indicators, objectives, scenarios, learning resources, media, models, methods, learning strategies, and evaluation tools need to be improved because there are many shortcomings to be able to strengthen the character of the nation. The role of teachers is very important for students to provide an understanding of what Corruption is and also plays a role in instilling values of honesty in students, so that students can carry out honest actions and not commit lies or acts of corruption. This study aims to provide an understanding to elementary school students that corruption is a reprehensible act and to find out how elementary school teacher education is implemented.